Acute Kidney Injury after Partial Nephrectomy of Solitary Kidneys: Impact on Long-Term Stability of Renal Function - Joseph Zabell (2019)
© 2018 American Urological Association Education and Research, Inc. Purpose: Acute kidney injury often leads to chronic kidney disease in the general population. The long-term functional impact of acute kidney injury observed after partial nephrectomy has not been adequately studied. Materials and Methods: From 2004 to 2014 necessary studies for analysis were available for 90 solitary kidneys managed by partial nephrectomy. Functional data at 4 time points included preoperative serum creatinine, peak postoperative serum creatinine, new baseline serum creatinine 3 to 12 months postoperatively and long-term followup serum creatinine more than 12 months postoperatively. Adjusted acute kidney injury was defined by the ratio, observed peak postoperative serum creatinine/projected postoperative serum creatinine adjusted for parenchymal mass loss to reveal the true effect of ischemia. The long-term change in renal function (the long-term functional change ratio) was defined as the most recent glomerular filtration rate/the new baseline glomerular filtration rate. The relationship between the grade of the adjusted acute kidney injury and the long-term functional change was assessed by Spearman correlation analysis and multivariable regression. Results: Median patient age was 64 years and median followup was 45 months. Median parenchymal mass preservation was 80%. Adjusted acute kidney injury occurred in 42% of patients, including grade 1 injury in 20 (22%) and grade 2/3 in 18 (20%). On univariable analysis the degree of the adjusted acute kidney injury did not correlate with the long-term glomerular filtration rate change (p = 0.55). On multivariable analysis adjusted acute kidney injury was not associated with a long-term functional change (p >0.05) while diabetes and warm ischemia were modestly associated with a long-term functional decline (each p <0.05). Conclusions: Acute kidney injury after partial nephrectomy was not a significant or independent predictor of long-term functional decline in our institutional cohort. A prospective study with larger sample sizes and longer followup is required to evaluate factors associated with long-term nephron stability.